Indonesian EFL Teachers’ Conceptions of Critical Thinking: Challenges, Strategies, and Implications for 21st-Century Education - Bachtiar Bachtiar (Universitas Muhammadiyah Enrekang, 2025)
Critical thinking (CT) has been widely recognized as a core 21st-century competency that equips learners to analyze, evaluate, and create knowledge rather than merely reproduce it. In the English as a Foreign Language (EFL) context, particularly in Indonesia, the integration of CT into classroom practices remains complex due to curricular, pedagogical, and systemic constraints. This study aimed to investigate Indonesian EFL teachers’ conceptions of CT, the challenges they face in integrating it into classroom instruction, and the strategies they adopt to promote it. Employing a qualitative descriptive design, data were collected from thirty-two senior high school EFL teachers through questionnaires and follow-up semi-structured interviews with eight participants. The findings revealed that while teachers generally acknowledged CT as essential for fostering problem-solving and independent learning, their understandings were fragmented and often reduced to surface-level interpretations. Teachers reported limited training, lack of clear assessment tools, and exam-oriented systems as significant obstacles, though some implemented strategies such as debates, case studies, and project-based learning. The study underscores the need for sustained professional development, curricular alignment, and institutional support to enable teachers to embed CT more systematically in EFL classrooms.